1988
DOI: 10.1007/bf01342639
|View full text |Cite
|
Sign up to set email alerts
|

Deep tectal cells in pigeons respond to kinematograms

Abstract: Deep tectal neurons in pigeons respond selectively to moving visual stimuli, and are inhibited by large background patterns moved in-phase with these stimuli. In this investigation we demonstrate that these same deep tectal neurons respond equally well to kinematograms as they do to traditional luminance contrast stimuli typically employed in visual experiments. Computer generated kinematograms, the motion domain equivalents of random dot stereograms, were used as stimuli in these experiments. These kinematogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…In this respect, FD cells have similar characteristics to cells found in the cat (Sterling and Wickelgren 1969), in the privet hawkmoth (Collett 1971;Collett and King 1975), in the pigeon (Frost and Nakayama 1983;Frost et al 1988) and in primates (Allman et al 1985;Tanaka et al 1986). Only two of the set of four FD cells are relevant in the present context: The FD1 and the FD4 cell are selective for front-to-back motion in front of the ipsilateral eye, i.e.…”
Section: Limitations In Simulating a Translatory¯ow ®Eldmentioning
confidence: 53%
See 1 more Smart Citation
“…In this respect, FD cells have similar characteristics to cells found in the cat (Sterling and Wickelgren 1969), in the privet hawkmoth (Collett 1971;Collett and King 1975), in the pigeon (Frost and Nakayama 1983;Frost et al 1988) and in primates (Allman et al 1985;Tanaka et al 1986). Only two of the set of four FD cells are relevant in the present context: The FD1 and the FD4 cell are selective for front-to-back motion in front of the ipsilateral eye, i.e.…”
Section: Limitations In Simulating a Translatory¯ow ®Eldmentioning
confidence: 53%
“…Landing occurred frequently when bees approached the edge facing the elevated side but hardly ever when they approached the edge facing the lower side, indicating that the landings on the edges are triggered by a local increase rather than by a decrease in motion speed perceived at the edge (Lehrer and Srinivasan 1993). Frost et al (1988) demonstrated that tectal cells in pigeons do not respond to random dot kinematograms in which an object solely de®ned by relative motion appeared as a``hole'' in the background, whereas they strongly respond to an object that appeared as elevated above the background. However, in the case of the kinematograms the depth impression was determined by the direction of motion of the border of a group of coherently moving dots making up the object, whereas in our case relative depth was de®ned on the basis of the relative velocities of object and background.…”
Section: Adaptations Of Object Detection Behaviour In The¯ymentioning
confidence: 99%
“…Of course, the area of the moving background must also be large enough to stimulate a large portion of the vi sual field [Kass and Kass,I960]. Previous investiga tions [Frost, 1978;Frost et al, 1981Frost et al, , 1988Tanaka et al, 1986] were not successful in eliciting this effect, perhaps due to the absence of one or more of these crit ical factors in the experimental conditions. In the present study, however, 29 out of 66 neurons (44%) exhibited motion after-responses, and it is not known why this phenomenon did not occur in the other neu rons (more than 56%).…”
Section: Discussionmentioning
confidence: 99%
“…These same neurons also fire well to kinematograms (which are the motion domain equivalents of random dot stereograms), when the configuration presented is equivalent to an object moving over the top of, or in front of, a background, thus breaking camouflage in cryptically patterned animals that are moving. These neurons, first found in pigeons, do not respond when kinemato-grams configured as holes or windows are presented to the same cells [Frost et al, 1988].…”
Section: Object or Animate Motionmentioning
confidence: 99%